Status of ossicular chain in cholesteatoma - Kabir, Abm Luthful; Hossain, Md Delwar; Biswas, Ashim Kumar; Ahmed, Mesbah Uddin; Pramanik, Dhiman (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To assess the ossicular changes in cholesteatoma both in children and in adults. Methods: This was a cross sectional comparative study which was carried out in the departments of Otolaryngology and Head-Neck Surgery of Bangabandhu Sheikh Mujib Medical University and Shaheed Suhrawardy Medical College Hospital during the period of January 2014 to December 2014. A total number of 55 patients having cholesteatoma were included in this study. Patients were divided into two groups according to their age. Age belonged to 18 years and more than 18 years were considered as group I (n=29) and group II (n=26) respectively. All patients were undergone Tympanomastoidectomy and all intraoperative findings were recorded. The two groups were compared with regard to extension of disease and status of ossicular chain. Results: In this study majority of patients were within 11-18 years in children group and within 19-30 years in adults group. Most of the children were male and female predominant in adult group. Extension of disease was significantly higher in children group. Ossicular erosion was also more frequent in children group. Conclusion: Extension of cholesteatoma and ossicular erosion was significantly higher in children group. Bangladesh J Otorhinolaryngol; April 2016; 22(1): 9-14